The role of thrushes in maintaining the genetic diversity and structure of a tropical palm - Carvalho, C. S. [UNESP]; Valverde, J.; Souza, M. [UNESP]; Ribeiro, T. [UNESP]; Nazareth, S. [UNESP]; Galetti, M. [UNESP]; Cortes, M. C. [UNESP] (Asociacion Espanola Ecologia Terrestre, 2019)
The extinction of large seed dispersers in fragmented habitats can affect the spatial, genetic and demographic structure of many plant species. We have studied seed dispersal and genetic diversity of Euterpe edulis in an Atlantic Forest fragment. Through focal observations we evaluated the quantity component of seed dispersal. In addition, in a plot of 25x50 m we genotyped all adults and a random sample of seedlings and seeds with the objective of characterizing the contribution of different adult plants to the seed rain, the fine-scale spatial genetic structure and the genetic diversity of seedlings and adults. Thrushes (Turdus spp.) were the main dispersers of this species. We did not observe any spatial genetic structure in seedlings or adults, although we did observe a stronger relationship between both stages below six meters. The values of inbreeding, expected heterozygosity and allelic richness were similar between seedlings and adults, demonstrating intergenerational stability in these parameters. Our results show that seed dispersed by thrushes occur mainly at short distance; nevertheless, the spatial overlap in the seed rain erodes the spatial genetic patterns that this process may generate. With this study, we demonstrate that these medium-sized birds are able to maintain genetic diversity between generations, giving them a crucial role in maintaining genetic diversity of zoochoric plants in fragmented landscapes.
Keywords: fragmentation; frugivores; seed rain; spatial genetic structure; palm head; Brazil